Development of Hybrid Learning-Based Storyboard Telling Media to Improve Students' Learning Understanding in Class 3 Ski Subjects MI Muhammadiyah 04 Moropelang - Fizatin Nisa; Nurdyansyah Nurdyansyah (Journal of Islamic and Muhammadiyah Studies, 2023)
The use of learning media is needed by teachers and students in delivering messages or information to be more effective and innovative. Storyboard telling is one of the right media to convey historical material chronologically or sequentially because it is chronological so that it can improve student understanding that is still abstract. This study aims to analyze the feasibility and description of the effectiveness of the development of storyboard telling media based on hybrid learning in ski subjects to improve the understanding of third grade students of MI Muhammadiyah 04 Moropelang. The type of research used in this research is research and development (research and development) with reference to the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques used are questionnaires/questionnaires, pretest and posttest, and documentation. Meanwhile, the data analysis technique used percentage quantitative analysis technique, and paired T-test analysis. The results of the feasibility test obtained by media experts are 88.57%, linguists are 90%, and content experts are 88% with an average eligibility of 89% with "very decent" qualifications. The results of the effectiveness test showed an increase in the pretest and posttest scores of 40.85% which were analyzed using a paired sample T-test with a probability value of 0.000 <0.05 so it can be concluded that the storyboard telling media based on hybrid learning can be said to be effective seen from there is a significant effect on students' understanding of learning in SKI class 3 MI Muhammadiyah 04 Moropelang subjects.